A framework for partner engagement: Episodes in the life of interorganizational partnerships. Issue 4 (2nd October 2022) - Vivek, Shiri D.; Dalela, Vivek; Ahmed, Muhammad Sohail
ABSTRACT: Scholars have widely studied engagement in consumer contexts, but research attention on engagement in interorganizational partnerships is lacking. The authors introduce the construct of partner engagement (PE) in business relationships–episodes of intense resource and social exchanges between two independent business entities directed toward common outcomes – and articulate its importance in understanding long-term collaborations. Hunt and Morgan's Resource-advantage (R-A) theory provides the theoretical underpinnings and rationale for the proposed PE framework. For this study, in-depth interviews were conducted to empirically develop the framework and propose the influence of environmental and relational factors in PE episodes. The article elaborates on the nature of PE and its influence on long-term collaboration. The implications for managing partnerships and advancing theory are discussed.